Prevalence of Intestinal Helminth Parasites of Dogs in Lagos, Nigeria - Ibidapo, Comfort Adejoke (Biological Sciences - PJSIR, 2005)
A survey of 310 dogs (164 males and 146 females) for infections with intestinal helminth parasites was carried out in Lagos, Southern Nigeria.Out of these, 175 were pet dogs and were routinely checked by veterinary doctors, while the remaining 135 were strayed-dogs, which did not receive medical check-up. Strayed-dogs were significantly more infected (77.8%) than the pet dogs (12.0%) at P < 01. The analysis of infection pattern, by age, revealed that among the strayed dogs, 92.2%, 76.6% and 59.5% of the puppies, young and adult dogs, respectively, were found infected. Corre- sponding prevalencies among the pet puppies, young and adult dogs were 21.5%, 7.1% and 5.0%. Helminth ova recovered from the strayed-dogs included Toxocara canis (47.6%), Ancylostoma caninum (41.9%), Dipylidium caninum (37.9%) and Trichuris vulpis (20.9%). Helminth ova recovered from the care-receiving dogs were Toxocara canis (5.8%), Ancylostoma caninum (3.2%) and Dipylidium caninum (2.1%). Female strayed-dogs, with a prevalence of 89.7%, were significantly more infected than their male counterparts (70.9%). Strayed-puppies, with an infection rate of 92.2%, were significantly more infected than strayed young and adult dogs. Public health implications of these results, with particular reference to zoonotic transmission, was highlighted.